2016
DOI: 10.1371/journal.pone.0165780
|View full text |Cite
|
Sign up to set email alerts
|

Defective Autophagy, Mitochondrial Clearance and Lipophagy in Niemann-Pick Type B Lymphocytes

Abstract: Niemann-Pick disease type A (NP-A) and type B (NP-B) are lysosomal storage diseases (LSDs) caused by sphingomyelin accumulation in lysosomes relying on reduced or absent acid sphingomyelinase. A considerable body of evidence suggests that lysosomal storage in many LSD impairs autophagy, resulting in the accumulation of poly-ubiquitinated proteins and dysfunctional mitochondria, ultimately leading to cell death. Here we test this hypothesis in a cellular model of Niemann-Pick disease type B, in which autophagy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 83 publications
0
41
0
Order By: Relevance
“…In parallel with these findings in NPC, there is also evidence of autophagy defects in NPA/B diseases (Fucho et al, 2014 ; Baulies et al, 2015 ; Canonico et al, 2016 ). For instance, hepatocytes from ASMase −/− mice exhibit impaired autophagy flux determined by the combination of rapamycin with or without chloroquine, an effect that was accompanied by increased LC3BII and p62 levels.…”
Section: Mitochondria-lysosomes Relationship and Mitochondrial Qualitmentioning
confidence: 67%
“…In parallel with these findings in NPC, there is also evidence of autophagy defects in NPA/B diseases (Fucho et al, 2014 ; Baulies et al, 2015 ; Canonico et al, 2016 ). For instance, hepatocytes from ASMase −/− mice exhibit impaired autophagy flux determined by the combination of rapamycin with or without chloroquine, an effect that was accompanied by increased LC3BII and p62 levels.…”
Section: Mitochondria-lysosomes Relationship and Mitochondrial Qualitmentioning
confidence: 67%
“…The inhibition of lysosomal-related functions renders the cell unable to degrade the overloaded defective proteins. Several studies demonstrated that many of these proteins are released via EVs to compensate their reduced degradation inside the cell [65]. In this context, an impairment of exosome biogenesis and secretion in neurodegenerative diseases caused by genetic mutations has been demonstrated [66].…”
Section: Exosomesmentioning
confidence: 99%
“…Cells were cultured at 37 • C and resuspended in pre-warmed (37 • C) medium containing 100 nM of LysoTracker (diluted in RPMI). After 45 min of incubation, red lysosomal fluorescence was detected by flow cytometry and confocal microscopy [97].…”
Section: Assessment Of Lysosomal Involvementmentioning
confidence: 99%